Elemental [videorecording (DVD)] - Sohn, Peter; Hoberg, John; Likkel, Kat (Kathryn Anne), 1962-; Hsueh, Brenda; Newman, Thomas, 1955- (Disney DVD, 2023)
An all-new, original feature film set in Element City, where fire-, water-, land- and air residents live together. The story introduces Ember, a tough, quick-witted, and fiery young woman, whose friendship with a fun, sappy, go-with-the-flow guy named Wade challenges her beliefs about the world they live in.